Overview on electro-chemical machining of super alloys. (2021) - Pawar, A.; Kamble, Dinesh; Ghorpade, R.R.
Abstract: With recent developments and benefits of electrochemical machining (ECM) such as No destruction of Tool, machining capabilities for complex shapes on difficult-to-cut materials and high machining efficiency at low cost has increased use in several manufacturing components (like in Turbine blades, Compressor blisk) mainly in the manufacture of aero-engine components. In this article, focus has been given on the key factors for machining super alloys such high temperature titanium alloys (BuRTi) used in aero-engines for electrochemical machining (ECM), Tool Materials used, Machining profiles and their influencing parameters (Voltage, Electrolyte concentration and frequency of tool vibration), hybrid methods of electro chemical machining. It is observed that a wide scope exists to focus on the developments in electrochemical machining ECM for machining titanium alloys for complex profiles, also to predict Anode shape and Dissolution characteristics of new advanced difficult-to cut materials. It is further expected to focus on Machining Contoured or Curved profile on High temperature BuRTi titanium alloys using STEM.